Marketing glocal': marketing global com estratégias locais como vantagem competitiva de mercado - Vaccari, Lara Coelho (2008)
The objective of this dissertation is to explore and deeply study the concepts about Glocal Marketing, explaining this recent phenomenon, highlighting the importance and the influence of local culture on the marketing mix of global organizations, in order to have successful commercialization of their products and services in different markets. Searching for a better understanding of Glocal Marketing became extremely important in the XXI Century, since there is an increase in the number of global companies which want to explore new markets in order to survive and remain in the highly competitive market. Concepts of Globalization, Marketing, Glocal Marketing, Culture are defined and explored. Also, the influence of culture on consumer behavior and on the marketing mix of global organizations is analyzed. The Hofstede¿s cultural typology is explained and it is used to give the reader an overview and a better understanding about the cultural influence in the acceptance of new products in new markets. The relationship between culture and marketing mix is discussed, as well as the importance of standardization versus customization of the marketing mix among countries with high cultural differences. The methodology is composed by descriptive research and a case study about a global organization, the Coca-Cola Company. Therefore, this dissertation aims to show and exemplify how the Coca-Cola Company applies glocal strategies on its marketing mix as a way to establish a competitive advantage in the market.